Rambu Tuka': Making Ready-to-Wear Clothes Inspired by Traditional Thanksgiving Ceremonies in Toraja Land - Sultana Putri; Nurul Hidayati (Universitas Negeri Medan, 2024)
Rambu Tuka' has the meaning Kameloan which means joy or happiness. For example, wedding ceremonies, tongkongan houses, and harvests. The process of the Rambu Tuka' event carried out by the Toraja community is followed by the Ma'letton ritual or what is known as the slaughtering of pigs, buffalo and chickens, then distributed to the community. Furthermore, the Pa'gellu Dance became a form of dance performed by the Toraja people during the Rambu Tuka' event. This ceremony is also carried out by the Toraja people as a form of gratitude to God for the gifts given. The uniqueness of the Rambu Tuka event then became a source of inspiration for the author in creating fashion works consisting of one ready-to-wear outfit. Clothing creation uses the Double Diamond Model process or double diamond model which consists of four creative processes, namely: (1) Discovery phase, (2) Define phase, (3) Development phase, (4) deliver. It is hoped that the results of this clothing creation will make people more familiar with the diversity of Indonesian culture, especially the uniqueness of the Rambu Tuka' ceremony.